User behaviors toward mobile video adoption in Taiwan: A qualitative study - Jia-Ling Lee (International Telecommunications Society (ITS), 2011)
This study was designed to examine users' usage behaviors toward mobile video adoption in Taiwan. A modified UTAUT (Unified Theory of Acceptance and Use of Technology) model was designed to be the theory basis to develop questionnaires and open-ended questions. Data were gathered from six participants from iOS and Android users, two experts, and one focus group with five members. The study was conducted from February to April, 2011. The findings in this study supported those in the literature review: Effort Expectancy and Perceived Playfulness factors had positive influence to users' usage behaviors. Facilitating Conditions and Performance expectancy also had positive effect to users' usage behaviors toward mobile video app adoption. Network quality issue was the concern and should be added in the model. Moreover, several implications and suggestions for mobile video app adoption were discussed in the study.
Keywords: 330; mobile video; Unified Theory of Acceptance and Use of Technology model (UTAUT); mobile video adoption; Taiwan